Standing and supine positions are better than sitting in improving rightward deviation in right-hemispheric stroke patients with unilateral spatial neglect: A randomized trial. Issue 46 (18th November 2022) - Onaka, Hitoshi; Kouda, Ken; Nishimura, Yukihide; Tojo, Hidenori; Umemoto, Yasunori; Kubo, Toshikazu; Tajima, Fumihiro; Mikami, Yukio
Abstract : Trial design: How body position affects unilateral spatial neglect (USN) is unclear. This cluster randomized trial aimed to examine the effects of different positions (supine, sitting, and standing) on USN in stroke patients. Methods: Twenty stroke patients (hemorrhage [n = 11], infarction [n = 9]) who were right-handed, had left hemiplegia due to right hemisphere damage that occurred within the last 2 years, and were in a state of arousal with a Glasgow Coma Scale score of 15 were included in the study. Table-top pen-and-pencil tests for USN (Bells Test, Line Bisection, Scene Copy, and Star Cancellation) were randomly conducted in the supine, sitting, and standing positions. Results: The mean values in each test were significantly smaller in the supine position than were those in the sitting position ( P = .015, .047, .015, and <.001), and those in the standing position were significantly smaller than those in the sitting position ( P = .007, <.001, =.006, and < .001). The results of the 4 tests in the standing position were similar to those in the supine position. Conclusions: Body position affects USN in stroke patients and that the standing and supine positions improve USN better than the sitting position. Some possible mechanisms are: muscle contractions in the lower limbs and the trunk could have affected results in the standing position, and reduction in gravitational stimulation in the supine position could have played a role.